Evaluating the Effects of Weed Control Methods on the Growth and Yield of Jackbean (Canavalia ensiformis l.) in South West Nigeria (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Field trials were conducted over three cropping seasons in 2013 to 2015, to evaluate the effect of weed control methods on the growth and yield of jackbean at the Federal University of Agriculture, Abeokuta, Nigeria (070 20′ N, 3o 23′ E, 159 m above sea level). The treatments were arranged in a randomized complete block design with three replications. Weed control treatments consisted of eight weed control methods viz: ProbabenR (prometryne + metolachlor, 200+200 g of a.i. per L), Super UnionR (prometryne + acetochlor, 130+380 g of a.i. per L) each applied at 2.4 kg a.i ha, 1.6 kg a.i/ha, 1.6 kg a.i/ha followed by supplementary hoe weeding, two hoe-weedings at 3 and 6 weeks after planting (WAP) and a weedy check. Data collected on jackbean growth and yield were subjected to analysis of variance (ANOVA), and treatment means separated using 5% least significant difference (LSD at p ≤ 0.05). Results showed that jackbean growth and yield were improved by the weed control treatments compared to untreated plots. Across the three years, plots treated with ProbabenR and Super UnionR plus supplementary hoe weeding led to maximum pod and kernel yields. Uncontrolled weeds led to 60.42%, 61.48% and 65.97% losses in number of pods, pod yield and kernel yield, respectively in jackbean compared to application of Super UnionR plus supplementary hoe weeding. The study concluded that application of ProbabenR at 1.6 kg a.i/ha and Super UnionR followed by hoe weeding proved more effective and can be adopted by farmers for improved jackbean production.